Celioscopic liver biopsy in silver catfish (Rhamdia quelen) - Feranti,João P.S. (2015)
Endosurgery has been used for assessment of fish celomatic cavity, as well as for obtaining biopsies for organic analysis. Such minimally invasive access may also be used for the analysis of environmental impact on biomarkers of pollution. In Brazil, studies and literature regarding the use of celioscopy in fish are sparse. The purpose of the current study was to develop a two-port celioscopy technique to obtain liver biopsy in silver catfish (Rhamdia quelen). Six adult female silver catfish were used. The animals were anesthetized and the inspection of the celomatic cavity were performed using a telescope and celioscopic-guided liver biopsy were taken using laparoscopic Kelly forceps. On the early postoperative period, the animals were released in a confined water reservoir where mortality could be checked. The liver samples were sent for histological assessment. There were no complications during surgery on early postoperative period. It was possible to visualize meticulously several organs (liver, spleen, stomach, pancreas, swim bladder, ovaries, bowel and transverse septum). In conclusion, the surgical technique and the anesthetic protocol proposed were suitable to perform liver biopsies in silver catfish and provided low morbidity.